Biharmonic Curves in a Strict Walker 3-Manifold - Mamadou Gningue; Ameth Ndiaye; Rénovat Nkunzimana (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study the geometry of biharmonic curves in a strict Walker 3-manifold and we obtain explicit parametric equations for biharmonic curves and time-like biharmonic curves, respectively. We discuss the conditions for a speed curve to be a slant helix in a Walker manifold. We give an example of biharmonic curve for illustrating the main result.